2001
DOI: 10.1046/j.1365-2141.2001.02828.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of factor VIII inhibitors in severe haemophilia: the importance of patient age

Abstract: Summary. The potential effect of age at the start of replacement therapy on the development of factor VIII (FVIII) inhibitors was assessed in 62 severe (FVIII , 2 IU/dl) haemophilia A patients who started FVIII therapy at one of two haemophilia centres. Inhibitors were tested on an annual basis. Persistent or high-titre inhibitors were detected in 15 patients (24%). Kaplan±Meier cumulative incidence at 3 years from first FVIII exposure was 41% (95% CI 22±67%) in patients starting therapy before the age of 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
145
2
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 21 publications
(27 reference statements)
6
145
2
5
Order By: Relevance
“…Both of the previous studies arbitrarily defined the strata of age at first FVIII exposure (>12, 12-7, £6 months), however, no significant trend was observed in this study by computing age at first FVIII exposure according to the same age strata (older than 12 months: reference; 12-7 months: OR 1AE1, 95% CI 0AE5-2AE6; 6 months or younger: OR 2AE2, 95% CI 0AE8-6AE2). Apart from the different study design, the main difference between this and previous studies is represented by the type of FVIII products used at the time of treatment onset: rFVIII in our series, low/intermediatepurity concentrates in the oldest patients and high-purity or recombinant products in the youngest patients of the two aforementioned series (Lorenzo et al, 2001;van der Bom et al, 2003). Furthermore, such confounders as the type of FVIII gene mutations and other environmental conditions were not taken into account in the previous studies (Lorenzo et al, 2001;van der Bom et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Both of the previous studies arbitrarily defined the strata of age at first FVIII exposure (>12, 12-7, £6 months), however, no significant trend was observed in this study by computing age at first FVIII exposure according to the same age strata (older than 12 months: reference; 12-7 months: OR 1AE1, 95% CI 0AE5-2AE6; 6 months or younger: OR 2AE2, 95% CI 0AE8-6AE2). Apart from the different study design, the main difference between this and previous studies is represented by the type of FVIII products used at the time of treatment onset: rFVIII in our series, low/intermediatepurity concentrates in the oldest patients and high-purity or recombinant products in the youngest patients of the two aforementioned series (Lorenzo et al, 2001;van der Bom et al, 2003). Furthermore, such confounders as the type of FVIII gene mutations and other environmental conditions were not taken into account in the previous studies (Lorenzo et al, 2001;van der Bom et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Apart from the different study design, the main difference between this and previous studies is represented by the type of FVIII products used at the time of treatment onset: rFVIII in our series, low/intermediatepurity concentrates in the oldest patients and high-purity or recombinant products in the youngest patients of the two aforementioned series (Lorenzo et al, 2001;van der Bom et al, 2003). Furthermore, such confounders as the type of FVIII gene mutations and other environmental conditions were not taken into account in the previous studies (Lorenzo et al, 2001;van der Bom et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a Spanish cohort of 62 children with severe (FVIII Ͻ 2 IU/dL) hemophilia A, 24% of whom developed persistent inhibitors, a statistically significant difference (P ϭ .03) in the cumulative incidence of laboratory-detected inhibitor formation based on age at first exposure was demonstrated. 4 A cohort study from the Netherlands of 81 infants with severe hemophilia A confirmed this trend, assessing the incidence at 100 exposure days. 5 This trend was again demonstrated in a larger multicenter review of 366 patients with severe hemophilia A in the Netherlands (the CANAL cohort study), but disappeared when adjusting for confounding factors, especially intensity at first treatment.…”
Section: Age At First Treatmentmentioning
confidence: 82%